Effectiveness of a Business Communication Course: Evidence From a Business School in India. (March 2015) - Gayathridevi, K. Sri; Deepa, R.
This study aims to show the effectiveness of a business communication course offered in a business school in India. All students who enrolled for the Master of Business Administration program in the school were considered for the study. The study adapted a pretest and posttest approach to find the effectiveness of the course. It also describes the curriculum offered and methodology followed in the school. The results show that the course was effective in improving the oral communication skills of the students. The study also discusses the implications for business schools, faculty, and students.